N-chlorotaurine is highly active against respiratory viruses including SARS-CoV-2 (COVID-19) in vitro. Issue 1 (31st December 2022) - Lackner, Michaela; Rössler, Annika; Volland, André; Stadtmüller, Marlena Nastassja; Müllauer, Brigitte; Banki, Zoltan; Ströhle, Johannes; Luttick, Angela; Fenner, Jennifer; Sarg, Bettina; Kremser, Leopold; Tone, Paul; et al.
ABSTRACT: N -chlorotaurine (NCT) a long-lived oxidant generated by leukocytes, can be synthesized chemically and applied topically as an anti-infective to different body sites, including the lung via inhalation. Here, we demonstrate the activity of NCT against viruses causing acute respiratory tract infections, namely severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), influenza viruses, and respiratory syncytial virus (RSV). Virucidal activity of NCT was tested in plaque assays, confirmed by RT-qPCR assays. Attack on virus proteins was investigated by mass spectrometry. NCT revealed broad virucidal activity against all viruses tested at 37°C and pH 7. A significant reduction in infectious particles of SARS-CoV-2 isolates from early 2020 by 1 log10 was detected after 15 min of incubation in 1% NCT. Proteinaceous material simulating body fluids enhanced this activity by transchlorination mechanisms (1 −2 log10 reduction within 1–10 min). Tested SARS-CoV-2 variants B.1.1.7 (Alpha) und B.1.351 (Beta) showed a similar susceptibility. Influenza virus infectious particles were reduced by 3 log10 (H3N2) to 5 log10 (H1N1pdm), RSV by 4 log10 within a few min. Mass spectrometry of NCT-treated SARS-CoV-2 spike protein and 3C-like protease, influenza virus haemagglutinin and neuraminidase, and RSV fusion glycoprotein disclosed multiple sites of chlorination and oxidation as the molecular mechanism of action. Application of 1.0% NCT as a prophylactic and therapeutic strategy against acute viral respiratory tract infections deserves comprehensive clinical investigation.